Parenting with Unintended Pregnancy in East Java, Indonesia: A Qualitative Study - Astuti, Sriwidi; Adi, Sapto; Puspita Ratih, Suci (KnE Life Sciences, 2021)
Teenage pregnancy is known to significantly impact the health of mothers and babies. Lack of preparations and poor knowledge might lead teenage mothers to have difficulties in practicing good parenting. Therefore, it is essential to assess parenting styles in adolescents with unwanted pregnancy (UP). This study aimed to analyse how teenage mothers with unwanted pregnancy nurture their babies. This research used a qualitative method with Rapid Assessment Procedure (RAP) study design. In-depth interviews, triangulations and observations were employed to obtain the data. Six informants participated in this study who were chosen purposively based on the inclusion criteria. The results showed that all informants took care of their babies by themselves. However, the majority of them showed inadequate exclusive breastfeeding (EBF), immunization and posyandu (Indonesian-integrated health post system) visit. Lack of informants’ understanding was found to be the leading factor of the inadequacies. Keywords: parenting, unintended pregnancy, adolescent, sexual health